2022
DOI: 10.3390/joitmc8020093
|View full text |Cite
|
Sign up to set email alerts
|

Using Online Grocery Applications during the COVID-19 Pandemic: Their Relationship with Open Innovation

Abstract: This present research examines the behavioral intentions of Filipinos to use online grocery applications during the novel COVID-19 pandemic. The study proposes an integration of the health belief model (HBM) and the Unified Theory of Acceptance and Use of Technology (UTAUT2) to identify the factors affecting the acceptance and usage of Filipinos of online grocery applications in terms of the impact of health risk for COVID-19. To accurately measure the factors and their relationship to behavioral intentions an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
24
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 70 publications
3
24
1
Order By: Relevance
“…As stated, several strategies may be developed based from the example to have a more entertaining, empathetic, user-friendly, and more options among users which would benefit customers and businesses to gain what they need. For example, it was suggested by Gumasing et al. (2022) how online grocery would provide ease of use, timely, and relevant day-to-day needs among users when the necessities and items needed are a single click.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As stated, several strategies may be developed based from the example to have a more entertaining, empathetic, user-friendly, and more options among users which would benefit customers and businesses to gain what they need. For example, it was suggested by Gumasing et al. (2022) how online grocery would provide ease of use, timely, and relevant day-to-day needs among users when the necessities and items needed are a single click.…”
Section: Discussionmentioning
confidence: 99%
“…To which, the presence of mediators and mediating effects can cause low to no significance ( German et al., 2022 ; Fan et al., 2016 ; Woody, 2011 ). Thus, machine learning algorithms may be employed to highlight the most significant factors that promotes linear relationship despite the presence of mediators ( Ong et al., 2022a ; Gumasing et al., 2022 ). One classification technique that produces a model with high accuracy that could be utilized is the random forest classifier (RFC).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Board 2 highlights the five authors, with the largest number of published articles and the title of their respective studies. However, it can be seen that an article can be authored by several authors, according to the article "Using online grocery applications during the Covid-19 pandemic: Their relationship with open innovation" by Gumasing et al (2022). According to Amankwah-Amoah (2021), despite the many academic contributions to the Covid-19 Pandemic, little attention was paid to the opportunities triggered by the crisis, as many industries were turned upside down and markets were uncertain, however, the crisis also is It is noteworthy that a lot of information has been learned and will serve as a model to deal with future pandemics, but a new sustainable model is needed (Hsu et al, 2020).…”
Section: Covid-19 Pandemic and Innovationmentioning
confidence: 99%
“…Ease of payment, for only small portion of Filipinos has credit cards, which is addressed via cash on delivery. (Go, 2017) A study conducted by Gumasing, et al (2022) examines the behavioral intentions of Filipinos to use online grocery applications during the novel COVID-19 pandemic. The results revealed that performance expectancy, perceived benefits, perceived severity, and cues to action significantly influenced the behavioral intentions and usage of online grocery apps during the COVID-19 pandemic.…”
Section: Introductionmentioning
confidence: 99%